NLRP3 Inflammasome Polymorphism and Macrovascular Complications in Type 2 Diabetes Patients - Jasna Klen; Katja Goričar; Andrej Janež; Vita Dolžan (Journal of Diabetes Research)
Background. It is generally accepted that poor glycemic control, arterial hypertension and/or hyperlipidemia, and the associated oxidative stress may contribute to the development of macro- and microvascular complications in type 2 diabetes (T2D). Such metabolic damage signals may activate inflammasome and trigger chronic inflammation. We investigated common polymorphisms in inflammasome coding genes and the risk for macro- and microvascular complications in T2D. Methods. In total 181 clinically well-characterised T2D patients were genotyped for NLRP3 rs35829419 and CARD8 rs2043211. Risk for diabetic complications was assessed using logistic regression. Results. Patients with median duration of T2D 11 (6–17) years had relatively well controlled blood glucose and lipid levels and blood pressure on the prescribed treatment regimen. Duration of T2D and plasma cholesterol levels were the most important clinical risk factors for macrovascular complications (P=0.007 and P=0.031). NLRP3 rs35829419 was associated with increased risk for macrovascular complications (P=0.004), with myocardial infarction in particular (P=0.052). No association was observed between CARD8 polymorphism and any of T2D complications. Conclusions. Our preliminary data suggest the role of NLRP3 polymorphism in diabetic macrovascular complications, especially in myocardial infarction.